Trajectory design and resource allocation for UAV energy minimization in a rotary-wing UAV-enabled WPCN - Wang, Zhen; Wen, Miaowen; Dang, Shuping; Yu, Lisu; Wang, Yuhao (Alexandria engineering journal, 2021)
Due to the low efficiency of energy harvest (EH) for the traditional wireless powered communication network (WPCN), we propose a communication scheme based on unmanned aerial vehicle (UAV)-enabled WPCN, which can greatly improve the EH efficiency problem. In this paper, the UAV trajectory, time allocation, transmit power of UAVs, scheduling of wireless information transfer (WIT) and wireless power transfer (WPT) are jointly optimized to minimize the whole energy consumption. To solve the formulated non-convex problem with multiple constraints and attain locally optimal solution, an iterative algorithm is proposed. Simulations show that our proposed algorithm is superior to other benchmark algorithms.